Food-related reward sensitivity across the spectrum of body weight and impulsive eating: Pilot findings from a multi-method approach. (1st February 2023) - Leehr, Elisabeth J.; Schag, Kathrin; Vogel, Jule; Dresler, Thomas; Zipfel, Stephan; Fallgatter, Andreas J.; Hautzinger, Martin; Dannlowski, Udo; Ehlis, Ann-Christine; Giel, Katrin E.
Abstract: Overweight with and without comorbid binge-eating disorder (BED) has been associated with increased reward sensitivity, though evidence is heterogeneous. To disentangle this heterogeneity and gain insights into mechanisms of impaired reward processing, this study applied multi-method neuro-behavioural techniques. Reward sensitivity was investigated in N = 49 participants allocated to three subgroups: overweight individuals with BED (BED+, n = 17), overweight individuals without BED (BED-, n = 15), and normal-weight controls (NWC, n = 17). Applying a free exploration paradigm (food vs. non-food stimuli), eye tracking and electroencephalographic data were gathered. A valid cue before stimulus onset indicated the position of food, and the end points analysed after the cue and stimulus onset were attentional approach, attention allocation, and conflict processing (e.g., conflict between looking at the potentially rewarding food stimulus or not). The effect of negative mood was tested using mood induction. The study's main hypothesis was that individuals with overweight, particularly under negative mood, would have increased food-related reward sensitivity. All participants showed increased food-specific attentional approach ( p < .001). BED + allocated more attention to food stimuli than non-food stimuli compared to the healthy control ( p = .045). For individuals with overweight but without BED (BED-), results indicate that conflict processing might be prolonged after the stimulus onset ( p = .011). No group-specific effect of negative mood was found. Preliminary results in overweight individuals with and without comorbid BED suggest that food stimuli are generally rewarding stimuli, but even more so for participants with binge eating psychopathology. Prolonged conflict processing during the confrontation with competing food and non-food stimuli was solely found in the BED- sample and might indicate a compensation mechanism. Replication is warranted. The multi-method approach seems to be promising to give indications for the development of psychotherapeutic treatment.